Associations of prenatal per- and polyfluoroalkyl substance exposure with neonatal birth weight z-scores: The potential mediating role of maternal glucose homeostasis - Chun-Yong Wang; Zhen-Hua Li; Hai-Yang Weng; Xiao-Yu Zhao; Shao-Lei Pu; Meng-Na Zhu; Rui He; Xia-Juan Lu; Yu-Long Kan; Kai Huang; Guo-Peng Gao; Mao-Lin Chen; et al. (Environmental Pollution, 2026)

L-proline enhances growth performance, digestive function and stress resistance of Chinese mitten crab (Eriocheir sinensis) larvae in high salinity-alkalinity rearing water - Cheng-yi Weng; Yu-xuan Zhao; An-jun Xiang; Yu-hai You; Huan Ma; Zhi-qiang Liu; Jian-yang Sun; Meng-jie Zhao; Chen Zheng; Yu-chen Chen; Yong-xu Cheng; Xiao-zhen Yang (Aquaculture, 2026)

Hierarchically cross-linked polyurethane derived from liquefied banana pseudo-stem with balanced mechanical robustness and multi-functionality - Fanrong Meng; Jun Cheng; Jingfa Zhang; Qiaoqiao Zhao; Peng Li; Honglei Chen; Yucang Zhang (Chemical Engineering Journal, 2026)

Low-frequency deficit irrigation in a semi-arid vineyard of Xinjiang's Manas region: Effects on grape and wine aroma composition across three vintages - Ning Shi; Meng-Bo Tian; Hao-Cheng Lu; Yi-Fan Zhao; Ming-Yu Li; Jia-Yi Deng; Chi-Fang Cheng; Shu-De Li; Zhen-Zhen Zhang; Keji Yu; Yi-Bin Lan; Fei He; et al. (Food Research International, 2026)

Novel dipeptidyl peptidase IV inhibitory peptides released from collagen by a unique protease A4095 with Y-Gly bond preference - Jun-Hui Cheng; Wen-Xiao Zhao; Hai-Yan Cao; Yan Wang; Jun-Wei Wang; Xiu-Lan Chen; Yu-Qiang Zhang; Meng Wang (Food Bioscience, 2026)

Egg Disease in Spodoptera litura (Fabricius) Caused by Aspergillus ochraceus and Its Metabolic Phenotype - Wen-Jie Lei; Yan Zhao; Qin-Ye Zhang; Hao-Jun Wang; Xiang-Li Dong; Jian-Yu Meng; Liu-Ti Cai; Hui-Zi Wu; Han-Cheng Wang (Current Microbiology, 2026)

Iridoid constituents from the flower buds and inflorescences of Buddleja officinalis and their anti-pulmonary fibrosis activity - Xiao-Yu Yuan; Xue Gong; Shi-Ying Yuan; Wei-Jin Meng; Chen-Hao Yu; Shao-Jun Wang; Xiao-Tian Zhang; Jun-Cheng Su; Luo-Sheng Wan (Phytochemistry, 2026)

Zinc regulates the balance of specific gut microbiota through MTF1/Nrf2 and mitigates ferroptosis through activation of PINK1/Parkin/mitophagy via the gut-kidney axis in sepsis-associated acute kidney injury in pregnant mice - Xingfeng Cheng; Yang Chen; Di Meng; Jie Ren; Xiaolong Yu; Huizhen Wang; Jun Guo (Apoptosis, 2026)

SYVN1-provoked RASA1 ubiquitination promotes pulmonary inflammation in chronic obstructive pulmonary disease - Ju-Hong Wu; Yi-Cheng Ma; Yu-Qi Wang; Hai-Long Miao; Meng-Xue Liu; Dong-Xu Hua; Min-Min Tang; Tian-Rui Sui; Zhi-Yong Wu; Yu Wang; Jin Yang; Hui Zhao; et al. (Inflammation Research, 2026)

Effects of exogenous N-acyl-homoserine lactones on biofilm formation by denitrifying bacteria and denitrification start-up in sequencing batch biofilm reactors - Zhi-fei Li; Meng-yuan Yu; Jun-lin Li; Jun Xie; Xiang-ju Cheng; Wang-bao Gong; Kai Zhang; Guang-jun Wang; Yun Xia; Wen-ping Xie; Quan-fa Zhong; Hong-yan Li; et al. (Journal of Environmental Chemical Engineering, 2026)

Carbonate-associated fluorescent dissolved organic matter (CAFDOM): Establishing a new proxy for dissolved organic matter in ancient oceans - Wei Wang; Chao Li; Matthew S. Dodd; Hao Xu; Meng Cheng; Zihu Zhang; Chunxia Yang; Jun Hu; Haiyang Wang; Xinyang Chen; Adrian Immenhauser (Geochimica et Cosmochimica Acta, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Genetic Diversity of Spodoptera litura in China Based on Mitochondrial DNA Analysis - Yu-Lin Li; Jian-Kun Long; Zhi-Ming Chang; Han-Cheng Wang; Jian-Yu Meng; Lin Yang; Jun-Yi Gao; Xiang-Sheng Chen (Phytoparasitica, 2026)

Discovery of notoprenylate F from Notopterygium incisum (Qianghuo) as a PPARγ agonist with potent anti-inflammatory activity through HTS2 - Meng-Dan Liu; Li-Jun Huang; Hao-Ran Lei; Yong-Jiang Wang; Yun-Jie Hu; Xue-Yan Huo; Cong-Cong Li; Li Huang; Li-Lian Zhao; Ming-Zhi Zhang; Yu-Cheng Gu; Melody Shyy; et al. (Marine Life Science & Technology, 2026)

System-dependent effects and mechanisms of microplastics/nanoplastics on nitrogen and phosphorus removal from wastewater treatment and N2O emission - Tong Wu; Shuai-Hang Wang; Ping Fang; Cheng-Xin Chen; Jie Ding; Ying He; Han-Jun Sun; Meng-Qi Ding; Ji-Wei Pang; Nan-Qi Ren; Shan-Shan Yang (Journal of Hazardous Materials, 2026)

Dynamic light exposure from afternoon shading reveals aromatic plasticity in grapes and wines from a semi-arid region - Meng-Bo Tian; Ning Shi; Hao-Cheng Lu; Ming-Yu Li; Jia-Yan Wei; Jia-Yi Deng; Chi-Fang Cheng; Shu-De Li; Fei He; Yi-Bin Lan; Chang-Qing Duan; Keji Yu; et al. (Food Chemistry, 2026)

Reservoir property estimation of interbedded sandstone and shale layers using segmented 3D rock-physics templates - Jing Ba; Xi-Ya Ba; Hong-Jing Dong; Jun-Wei Cheng; Cong Luo; Zhi-Fang Yang; Meng-Qiang Pang; Wen-Hui Tan (Applied Geophysics, 2026)

Research progress on chemical constituents and biological activities of medicinal plants from Euonymus genus - Ying-Jun Ma; Xin-Ru Li; Meng-Qi Gao; Jia-Jia Liu; Ammara Khalid; Jie-Ting Chen; Fan-Cheng Meng (Natural Product Research, 2026)

TRAF7 protects against acute lung injury by promoting K6-linked ubiquitination of AKT - Jia Wang; Meng-Liu Zeng; Ya-Zhou Sun; Xu-Tao Zhang; Xin-Yan Li; Wei-Yi Qu; Wei Li; Jia-Yi Liu; Xu Cheng; Jun Zhang; Han Tian; Hui Liu; et al. (Science Bulletin, 2026)

Nano-bio interaction determines the early progression of lung cancer by reshaping pulmonary epithelial microenvironment - Yu-Han Zhang; Jun Zhang; Lei Shi; Meng Xiang; Xue Han; Ling Zhu; Jia-Cheng Xie; Yan Chen; Qi Gu; Jing-Yu Li; Zhen Zou; Jian-Yu Wang (Journal of Hazardous Materials, 2026)

Associations between PM2.5 components, temperature, and semen quality: Insights from seminal plasma metabolome - Jun-feng Tan; Li-li Huang; Zhong-Hua Lu; Hang-Yu Xiang; Hong Yang; Hai-Xia Zhou; Tian-qing Meng; Cheng-liang Xiong; Yi-Xin Wang; Jie Zhang (Environmental Research, 2025)

Development and validation of a magnetic - based corrosion detection system for reinforced concrete structures - Jian Cheng; Yu-meng Xie; Rong-sen Gao; Ye Tian; Guo-yi Zhang; Dongming Yan; Bo Chen; Ruo-yi Zhao; Bei Li; Jun Chen; Dong-yang Cai; Wei-qiang Wu; et al. (Engineering Structures, 2025)

Vancomycin nanocomposite-functionalized M2 macrophages for precision targeting of MRSA in prosthetic joint infections - Ling Wu; Weijing Cheng; Bingkun Meng; Han Yan; Jun Liu; Fengze Miao; Tingrui Zhang; Xinyue Zhang; Nan Ding; Yujing Zhao; Quangang Zhu; Ziqiang Chen; et al. (Chemical Engineering Journal, 2025)

Application of ambient noise tomography to coastal granite islands: A case study of Wuzhizhou Island in Hainan, China - Cheng Huang; Sheng Liu; Jun-Qiao Long; Chang-Rong Zhang; Bo Xiao; Da-Cheng Wang; Cheng-Long Wei; Rui Wang; Li Yan; Xuan Hu; Zhuo Xin; Xiu-Ji Meng; et al. (Applied Geophysics, 2025)

The new ten-numbered macrolide, diaporthsin L, from endophytic fungus Diaporthe sp. G-4 isolated from Strobilanthes cusia (Nees) Kuntze - Jun-yi Li; Zhen-xian Cun; Hui-hui Sun; Jie-Zheng Shi; Wen-xiang Yan; Jun-meng Xia; Dong Gan; Mao-ru Li; Ju-cheng Zhang; Zhong-tao Ding (Natural Product Research, 2025)

Flavoromics analysis and sensory evaluation of wines produced from nine red grape cultivars in Manas region, Xinjiang, China: Implications for terroir adaptation - Ning Shi; Yi-Fan Zhao; Hao-Cheng Lu; Meng-Bo Tian; Ming-Yu Li; Jia-Yi Deng; Jia-Yan Wei; Ai-Sai Chen; Chi-Fang Cheng; Shu-De Li; Fei He; Keji Yu; et al. (Food Chemistry, 2025)

Regional airflow velocity control to meet the diverse requirements of unevenly distributed maize threshing mixtures - Meng Zhang; Chao Cheng; Jun Fu; Zhi Chen; Luquan Ren (Biosystems Engineering, 2025)

AhR-mediated histone lactylation drives cellular senescence during benzo[a]pyrene-evoked chronic obstructive pulmonary disease - Li-Hong Chen; Jun-Ping Wei; Meng-Die Li; Xiu Lu; Yi-Cheng Ma; Yu Wang; Ling Zheng; Jun Fei; Wei Cao; De-Xiang Xu; Jin Yang; Hui Zhao; et al. (Journal of Hazardous Materials, 2025)

Zinc isotopic evidence for enhanced oceanic primary productivity during termination of the late Ediacaran Shuram Excursion - Jinzuo Tong; Meng Cheng; Jun Hu; Xinyang Chen; Haiyang Wang; Thomas J. Algeo; Mingcai Hou; Chao Li (Geochimica et Cosmochimica Acta, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Evolution analysis of key mechanical properties during the forming process of JCOE and JCOC pipes and its influence on collapse failure - Shaocong Qi; Guoyi Shen; Xihai Liu; Wanlin Cheng; Ruixue Zhai; Qingdang Meng; Jun Zhao; Gaochao Yu (Ocean Engineering, 2025)

A method on the induction of piezoelectricity of PVDF by NaOH: Induced PVDF as ultrafiltration base membrane in interfacial polymerization to enhance the rejection of NaCl - Yuliang Chen; Wenmin Wang; Ying Liang; Chen Chen; Rui Meng; Libo Ba; Yuliang Wu; Yijiang Liu; Weiwei Huang; Fei Yang; Jun Cheng; Xuesong Yi (Desalination, 2025)

Preparation of polyester amide nanofiltration membrane by low concentration hydroxyl monomer induced piperazine through intermolecular interaction - Yuliang Wu; Rui Meng; Chen Chen; Yuliang Chen; Libo Ba; Yijiang Liu; Weiwei Huang; Fei Yang; Jun Cheng; Xuesong Yi; Shitao Zhi; Yajie Pang (Desalination, 2025)

Effect of rootstocks on growth potential, soil properties and rhizosphere microbiome of Vitis vinifera L. cv. Cabernet Sauvignon - Ning Shi; Xiao Han; Hao-Cheng Lu; Meng-Bo Tian; Ming-Yu Li; Fei He; Chang-Qing Duan; Ke-Ji Yu; Jun Wang (Plant and Soil, 2025)

Exploring possible ancient applications of perilla: evidence from 3 million fruit remains from Han Dynasty tombs in China - Yun-Jun Bai; Ming Jiang; Xue-Ping Wei; Zhi-Jun Zhao; Xin-Ying Zhou; Hong-En Jiang; Tao Xie; Xiao-Lin Li; Yu-Yang Zhao; Xue Yan; Meng Cheng; Lu-Qi Huang; et al. (Science Bulletin, 2025)

Machine learning-based generation of high-resolution 3D full-coverage aerosol distribution data over China using multisource data - Wenze Li; Wenchao Han; Jiachen Meng; Zipeng Dong; Jun Xu; Qimeng Wang; Lulu Yuan; Han Wang; Zhongzhi Zhang; Miaomiao Cheng (Remote Sensing of Environment, 2025)

Reconciling redox proxy contradiction with active Fe Mn shuttle in the Cryogenian Nanhua Basin of South China - Meng Cheng; Zihu Zhang; Jun Hu; Haiyang Wang; Mengchun Cao; Chao Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Size-dependent internalization of polystyrene microplastics as a key factor in macrophages and systemic toxicity - Wei-Qiang Luo; Meng-Ting Cao; Chen-Xuan Sun; Jun-Jian Wang; Meng-Xi Gao; Xue-Rui He; Le-Ning Dang; Yang-Yang Geng; Bing-Yao Li; Jing Li; Zhi-Cheng Shi; Xing-Rong Yan (Journal of Hazardous Materials, 2025)

Subducted sediment recycling and fractional crystallization of the Toba volcanic system constrained by plagioclase geochemistry - Meng-Hao Gao; Ping-Ping Liu; Dian-Bing Wang; Xi-Jun Liu; Gui-Bin Zhang; Cheng Xu (Chemical Geology, 2025)

Characteristics of Energy Evolution and Strength Degradation of JINPING Marble in Multi-stage Compression Tests with Sustained Loading - Chen Fan; Xia-Ting Feng; Jun Zhao; Cheng-Xiang Yang; Meng-Fei Jiang (Rock Mechanics and Rock Engineering, 2025)

New Colorimetric Chemosensor for Rapid Naked-Eye Detection of Cu2+ and Its Application in Gas-Generating Agents - Xiaohong Cheng; Jun You; Shaoyong Meng; Wenjie Shen; Tao Du; Wenbin Fu; Yunqiang Luo; Song Wang (Journal of Fluorescence, 2025)

A new insight into the transformation mechanism between reactivity of aqueous monomer and chlorine resistance of polyester-amide nanofiltration membrane - Yuliang Wu; Rui Meng; Chen Chen; Yuliang Chen; Libo Ba; Yijiang Liu; Weiwei Huang; Fei Yang; Yanshan Wang; Jun Cheng; Xuesong Yi; Heng Liang (Desalination, 2025)

Anti-hypoxia polyacetylenes and sesquiterpenoids from Codonopsis pilosula (Franch.) Nannf - Zhuo-Yang Cheng; Jun-Ge Jin; Meng Yan; Xin-Yue Chen; Jian-Kuan Li; Jian-Ping Gao; Jiang-Tao Zhou (Natural Product Research, 2025)

60Co-γ-ray-irradiated edible silkworm (Bombyx mori) pupae-assisted protease digestion: A strategy for obtaining low molecular weight bioactive peptides - Xiao-Meng Xun; Cheng-Hai Yan; Zi-Xuan Yuan; Zhi-Ang Zhang; Richard Ansah Herman; Yan Xu; Qiong-Ying Wu; Jun Wang (Sustainable Chemistry and Pharmacy, 2025)

Vertical and lateral bearing performance of bidirectional Helix-Stiffened cement mixing piles on marine soft soil sites: Field tests and numerical simulations - Jun-nan Zhao; Zhong-ling Zong; Yun-han Huang; Meng-meng Lu; De-long Huang; Cheng-yu Guo (Ocean Engineering, 2025)

Geochemistry and U–Pb geochronology of the granite porphyry in Bainiuchang, Southeastern Yunnan, China - Nan Shi; Jun Zhu; Xuelong Liu; Shitao Zhang; Guangzhi Meng; Hong Zhang; Jialong Cheng; Jiehu Zhou; Bode Lu; Junshan Dao; Xue Mi; Maohuang Fan (Acta Geochimica, 2025)

Dietary retinoic acid improved the growth, lipid metabolism and immune status in Macrobrachium rosenbergii - Qin-Cheng Huang; Li Wang; Zhi-Min Gu; Cui Liu; Tian-Tian Ye; Jun-Jun Yan; Ji-Lun Meng; Yu-Tong Zheng; Xian-Ping Ge; Zhi-Deng Lin; Guo-Yuan Zou (Frontiers in Marine Science, 2025)
The effect of dietary retinoic acid (RA) on the growth, lipid deposition, oxidation resistance, immunity, hepatopancreatic and intestinal health of Macrobrachium rosenbergii was evaluated. A total of 1200 prawns (0.22 ± 0.00 g) were divided into six groups and fed their corresponding feed containing 4, 132, 296, 562, 1206 or 2562 mg/kg dietary RA. The weight gain rate, specific growth rate and final body weight of the prawns changed linearly and quadratically, with the maximum observed in those fed 296 mg/kg dietary RA. Increasing dietary RA linearly and quadratically raised the RA content in the whole body. Compared to the prawns fed 4 mg/kg dietary RA, there was significantly lower lipid deposition in the muscle, hepatopancreas and whole body of prawns fed 296 mg/kg dietary RA. Prawns fed 296 mg/kg dietary RA had lower triglyceride (TG) content in the hepatopancreas with upregulated gene expression of retinoid X receptor ( RXR ), diacylglycerol acyltransferase 1 ( dgat1 ) and carnitine palmitoyltransferase 1 ( cpt1 ). Additionally, 296 mg/kg dietary RA increased the protein expression of RXR, CAMKKβ and phospho-AMPK. A dietary RA level of 296 mg/kg could decrease oxidative stress by upregulating the expression of peroxiredoxin 5 ( prx5 ) and improve immunity by upregulating expression of toll - like receptor 2 ( toll2 ), myeloid differentiation factor 88 (myd88 ) and dosal in the hepatopancreas. The intestinal health related genes ( crustin 2 / 3 / 4 , anti-lipopolysaccharide factor 1 / 7 , prx5 , peritrophin-1 , myosin light chain kinase , claudin , myd88 and dosal ) and morphological structure were also positively affected by dietary RA. Furthermore, dietary RA could relieve the immune responses induced by lipopolysaccharide, thus leading to lower transcription of antimicrobial peptides. In summary, dietary RA could improve the growth, lipid utilisation, antioxidant capacity and immunity of M . rosenbergii . To avoid the negative effects of excessive addition and obtain optimal growth, a diet containing 296 mg/kg dietary RA was suggested by the present study.

Mechanism study of the effect of a surface liquid film on the collision adhesion behaviour of rice stalks - Jun Fu; Meng Zhang; Chao Cheng; Haiming Zhao; Luquan Ren (Biosystems Engineering, 2025)

Mid-late Holocene meridional out-of-phase precipitation patterns in the margin of the East Asian monsoon region revealed by paleoclimate records and simulations - Fengyi Zhang; Jun Cheng; Weiwei Sun; Xianqiang Meng; Zhenyu Ni; Yao Wang; Enlou Zhang (Quaternary Science Reviews, 2025)

Environmental DNA/RNA metabarcoding for noninvasive and comprehensive monitoring and assessment of marine fishes - Peiyuan Ye; Jinping Cheng; Linus Shing Him Lo; Jingyu Liu; Chao Li; Kelvin Jun Yin So; Fei Xia; Meng Yan; Junjie Wang; Clara U; Jian-Wen Qiu; Wenlong Cai; et al. (Marine Pollution Bulletin, 2025)

Sequential decline in cyanobacterial, total prokaryotic, and eukaryotic responses to backward flow in a river connected to Lake Taihu - Jun Zuo; Siyu Yang; Hans-Peter Grossart; Peng Xiao; He Zhang; Rui Sun; Guoyou Li; Haoran Jiang; Qihang Zhao; Meng Jiao; Yao Cheng; Zeshuang Wang; et al. (Water Research, 2025)

A novel zearalenone lactonase can effectively mitigate zearalenone-induced reproductive toxicity in gilts - Jun-Chao Song; Zhe Peng; Yan-Qi Ning; Alainaa Refaie; Cheng-Fei Wang; Meng Liu; Lv-Hui Sun (Toxicon, 2025)

Meso-mechanical mechanism of ordered mica alignment on the progressive failure process of granite under different lateral stress directions - Chen Fan; Xia-Ting Feng; Jun Zhao; Cheng-Xiang Yang; Meng-Fei Jiang (International Journal of Rock Mechanics and Mining Sciences, 2025)

Time-Dependent Asymmetric Instability in a Deep TBM Tunnel Due to the Combination of Mesoscopic Rock Heterogeneity and Triaxial Stress - Chen Fan; Xia-Ting Feng; Jun Zhao; Cheng-Xiang Yang; Meng-Fei Jiang (Rock Mechanics and Rock Engineering, 2025)

Effects of UV-A irradiation and microbial fermentation on the physicochemical, microstructure and functional properties of okara - Ya-Ting Lei; Fan-Bing Meng; Xiao-Lei Jiao; Yuan-Mou Tang; Qi-Jun Wu; Yun-Cheng Li (Food Research International, 2025)

Simple and eco-friendly fabrication of hempseed protein by one-step low-temperature-induced phase separation and centrifugal removal of oil - Na Qin; Jin-Ting Deng; Jia-Jun Liao; Xiao-Ling Liu; Meng-Fan Lv; Hao-Yu Yuan; Cheng-Hua Wang (Food Hydrocolloids, 2025)

Aromatic Chinese medicine-decorated mesoporous nanoenzyme overcomes multiple biological barriers for solid tumor treatment - Xiaolong Quan; Ben Hu; Yibing Li; Iman Zare; Fengyong Cheng; Huiqi Huang; Jun Liu; Peng Cao; Dan Zhou; Meng Yu (Chemical Engineering Journal, 2025)

Pyridoxine supplementation before puberty ameliorates MAM-induced cognitive and sensorimotor gating impairments - Cheng Xue; Xiao-Hui Li; Hong-Qun Ding; Xin Qian; Meng-Yu Zhang; Kai Chen; Zi-Wei Wei; Ying Li; Jun-Hai Jia; Wei-Ning Zhang (Metabolic Brain Disease, 2024)

Thickness monitoring of threshing mixture on the oscillating plate of corn grain harvester - Jun Fu; Meng Zhang; Chao Cheng; Haiming Zhao; Luquan Ren (Computers and Electronics in Agriculture, 2024)

Development and validation of a potential risk area identification model for hand, foot, and mouth disease in metropolitan China - Xu Guang; Yifei He; Zhigao Chen; Hong Yang; Yan Lu; Jun Meng; Yanpeng Cheng; Nixuan Chen; Qingqing Zhou; Rongxin He; Bin Zhu; Zhen Zhang (Journal of Environmental Management, 2024)

Volatilomics of Cabernet Sauvignon grapes and sensory perception of wines are affected by canopy side in vineyards with different row orientations - Hao-Cheng Lu; Meng-Bo Tian; Ning Shi; Hui-Qing Li; Ming-Yu Li; Chi-Fang Cheng; Wu Chen; Shu-De Li; Fei He; Chang-Qing Duan; Andrea Schubert; Jun Wang (Food Chemistry, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

A novel cascade catalysis for one-pot enzymatically modified isoquercitrin (EMIQ) conversion from rutin and sucrose using rationally designed gradient temperature control - Yu-Fan Zhan; Zhuo-Hao Meng; Cheng-Hai Yan; Min Tan; Marriam Khurshid; Yi-Jiangcheng Li; Shao-Jun Zheng; Jun Wang (Food Chemistry, 2024)

Fabrication of passive cooling fabric as thermal management curtain for building energy-saving - Chao-Qun Ma; Chao-Hua Xue; Xiao-Jing Guo; Wenzhao Shi; Hui-Di Wang; Meng-Chen Huang; Li Wan; Yong-Gang Wu; Jun Cheng (Chemical Engineering Journal, 2024)

Effective waste management through Co-pyrolysis of EFB and tire waste: Mechanistic and synergism analysis - Guo Ren Mong; Chin Seng Liew; Rubia Idris; Kok Sin Woon; William Woei Fong Chong; Meng Choung Chiong; Jun Wei Lim; Cheng Tung Chong; Chew Tin Lee; Keng Yinn Wong; Andrew Kay Lup Ng (Journal of Environmental Management, 2024)

Scalable thermochromic superhydrophobic collagen fiber-based wearable materials for all-weather self-adaptive radiative cooling and solar heating - Meng-Chen Huang; Chao-Hua Xue; Zhongxue Bai; Hui-Di Wang; Chao-Qun Ma; Yong-Gang Wu; Li Wan; Long Xie; Shi-Qiang Lv; Rong-Rong Gao; Wen-Min Zhang; Jun Cheng; et al. (Chemical Engineering Journal, 2024)

Genomic analysis of Alteromonas sp. M12 isolated from the Mariana Trench reveals its role in dimethylsulfoniopropionate cycling - Yue Lin; Min Zhang; Yu-Xiang Lai; Teng Liu; Meng Meng; Yan Sun; Yu Wang; Qing-Yu Dong; Chen-Xi Li; Meng-Xue Yu; Jin Cheng; Shu-Jun Liu; et al. (Marine Genomics, 2024)

Field investigation of unsaturated hydraulic conductivity using actively heated fiber-optic technology - Jie Liu; Yu-Jun Cui; Meng-Ya Sun; Kai Gu; Jun-Cheng Yao; Chao-Sheng Tang; Bin Shi (Journal of Hydrology, 2024)

Heterogeneous coupling of δ13Corg and δ13Ccarb during the Shuram Excursion: Implications for a large dissolved organic carbon reservoir in the Ediacaran ocean - Haodong Gu; Jun Hu; Meng Cheng; Haiyang Wang; Matthew S. Dodd; Zihu Zhang; Thomas J. Algeo; Chao Li (Global and Planetary Change, 2024)

Mulberry (Morus alba L.) leaf powder modified the processing of meat alternatives: Principal component analysis from apparent properties to chemical bonds - Zhi-Ang Zhang; Xiao-Meng Xun; Richard Ansah Herman; Zhan-Peng Zhang; Cheng-Hai Yan; Lu-Chan Gong; Jun Wang (Food Chemistry, 2024)

Characterization of HIPEs stabilized by soy protein isolate with excellent rheological properties for 3D printing: Bridging the correlation among structure, function and application - Meng Yuan; Bailiang Li; Fuwei Sun; Tianfu Cheng; Jun Liu; Daoying Wang; Zengwang Guo; Zhongjiang Wang (Food Hydrocolloids, 2024)

Wave, flow, and suspended sediment dynamics under strong winds on a tidal beach - Lingpeng Meng; Junbiao Tu; Xiaodong Wu; Sha Lou; Jun Cheng; Sergey Chalov; Xiangju Han; Daidu Fan (Estuarine, Coastal and Shelf Science, 2024)

Effects of silvopastoral systems on soil nutrient properties in the low hilly area of western Henan province, China - Peisong Liu; Fan Cheng; Jun Hu; Meng Li; Xinlong Wang; Shirong You; Weishuang Tong; Liping Cheng; Jinping Zhang; Lixuan Kou (Agroforestry Systems, 2024)

Combined effects of cadmium and sulfamethoxazole on Eisenia fetida: Insights into accumulation, subcellular partitioning, biomarkers and toxicological responses - Sheng-Nan Zhang; Yi-Tong Zhou; Jun Xia; Yu-Meng Wang; Jun-Wei Ma; Li-Kun Wang; Kashif Hayat; Shan-shan Bai; Cheng-han Li; Ming-Rong Qian; Hui Lin (Science of The Total Environment, 2024)

An engineered DNA aptamer-based PROTAC for precise therapy of p53-R175H hotspot mutant-driven cancer - Lingping Kong; Fanlu Meng; Ping Zhou; Ruixin Ge; Xiaoshan Geng; Zhihao Yang; Guo Li; Linlin Zhang; Jing Wang; Jinfeng Ma; Cheng Dong; Jun Zhou; et al. (Science Bulletin, 2024)

Overexpression of the grape β-galactosidase gene VvBGAL3 delays the softening and extends the shelf life of tomato fruits - Shanshan He; Hongli Wei; Zhirui Xue; Meng Li; Jiannan Xie; Jiakang Qian; Xing Chen; Zhiqian Li; Chang He; Bin Tan; Xianbo Zheng; Jun Cheng; et al. (Postharvest Biology and Technology, 2024)

Predicting the deformation of compacted loess used for land creation based on the field monitoring with fiber-optic technology - Jie Liu; Bin Shi; Yu-Jun Cui; Meng-Ya Sun; Kai Gu; Jun-Cheng Yao; Chao-Sheng Tang (Engineering Geology, 2024)

Development of high-performance nitrile hydratase whole-cell catalyst by automated structure- and sequence-based design and mechanism insights - Meng Li; Dong Ma; Jun Qiao; Zhongyi Cheng; Qiong Wang; Zhemin Zhou; Laichuang Han (Systems Microbiology and Biomanufacturing, 2024)

A rapid and efficient Agrobacterium-mediated transient transformation system in grape berries - Jiannan Xie; Chang He; Zhiqian Li; Meng Li; Shanshan He; Jiakang Qian; Bin Tan; Xianbo Zheng; Jun Cheng; Wei Wang; Jidong Li; Jiancan Feng; et al. (Protoplasma, 2024)

Time-dependent nonmonotonic concentration-response and synergism of alkyl glycosides with different alkyl side chain to Vibrio qinghaiensis sp. -Q67 - Meng-Ting Tao; Shu-Shen Liu; Ting-Ting Ding; Zhong-Wei Gu; Ru-Jun Cheng (Science of The Total Environment, 2024)

PM2.5 exposure-induced senescence-associated secretory phenotype in airway smooth muscle cells contributes to airway remodeling - Pei-Pei Cheng; Fan Yu; Shuai-Jun Chen; Xiao Feng; Zi-Heng Jia; Shi-He Hu; Xiao-Lin Cui; Ya-Ya Zhou; Qian Niu; Li-Mei Liang; Meng Wang; Lin-Jie Song; et al. (Environmental Pollution, 2024)

The pH adjustment of Vitis amurensis dry red wine revealed the evolution of organic acids, volatomics, and sensory quality during winemaking - Meng-Bo Tian; Rui-Qi Hu; Zhao-Long Liu; Ning Shi; Hao-Cheng Lu; Chang-Qing Duan; Jun Wang; Yan-Feng Sun; Qing-Sen Kong; Fei He (Food Chemistry, 2024)

Genetic architecture of ecological divergence between Oryza rufipogon and Oryza nivara - Qing‐Lin Meng; Cheng‐Gen Qiang; Ji‐Long Li; Mu‐Fan Geng; Ning‐Ning Ren; Zhe Cai; Mei‐Xia Wang; Zi‐Hui Jiao; Fu‐Min Zhang; Xian‐Jun Song; Song Ge (Molecular Ecology, 2024)
Ecological divergence due to habitat difference plays a prominent role in the formation of new species, but the genetic architecture during ecological speciation and the mechanism underlying phenotypic divergence remain less understood. Two wild ancestors of rice ( Oryza rufipogon and Oryza nivara ) are a progenitor‐derivative species pair with ecological divergence and provide a unique system for studying ecological adaptation/speciation. Here, we constructed a high‐resolution linkage map and conducted a quantitative trait locus (QTL) analysis of 19 phenotypic traits using an F 2 population generated from a cross between the two Oryza species. We identified 113 QTLs associated with interspecific divergence of 16 quantitative traits, with effect sizes ranging from 1.61% to 34.1% in terms of the percentage of variation explained (PVE). The distribution of effect sizes of QTLs followed a negative exponential, suggesting that a few genes of large effect and many genes of small effect were responsible for the phenotypic divergence. We observed 18 clusters of QTLs (QTL hotspots) on 11 chromosomes, significantly more than that expected by chance, demonstrating the importance of coinheritance of loci/genes in ecological adaptation/speciation. Analysis of effect direction and v ‐test statistics revealed that interspecific differentiation of most traits was driven by divergent natural selection, supporting the argument that ecological adaptation/speciation would proceed rapidly under coordinated selection on multiple traits. Our findings provide new insights into the understanding of genetic architecture of ecological adaptation and speciation in plants and help effective manipulation of specific genes or gene cluster in rice breeding.

A mild and efficient sonothermal tumor therapy enhanced by sonodynamic effect with biodegradable red phosphorus nanoparticles - Zhizi Ma; Meng Yuan; Ziyong Cheng; Zhuang Yang; Ling Yang; Bin Liu; Yulong Bian; Abdulaziz A. Al Kheraif; Ping'an Ma; Jun Lin (Chemical Engineering Journal, 2024)

Vineyard soil heterogeneity and harvest date affect volatolomics and sensory attributes of Cabernet Sauvignon wines on a meso-terroir scale - Hao-Cheng Lu; Meng-Bo Tian; Xiao Han; Ning Shi; Hui-Qing Li; Chi-Fang Cheng; Wu Chen; Shu-De Li; Fei He; Chang-Qing Duan; Jun Wang (Food Research International, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Epoxy-based high-k composite vitrimer: With low dielectric loss, high breakdown strength and surface electrical damage repairability - Yu-Cheng Zhang; Wen-Dong Li; Xin Zhao; Fan-Bo Meng; Peng Sun; Chao Wang; Guang-Zhi Guo; Wen-Rui Li; Guan-Jun Zhang (Chemical Engineering Journal, 2023)

Psychromarinibacter sediminicola sp. nov., a novel moderately halophilic, metabolically diverse bacterium isolated from a solar saltern sediment, and comparison between members of family Roseobacteraceae - Yu-Hui Wang; Jun-Cheng Liu; Yi-Heng Du; Jin-Hao Xu; Zong-Jun Du; Meng-Qi Ye (Archives of Microbiology, 2023)

Genetic deletion or pharmacological inhibition of soluble epoxide hydrolase attenuated particulate matter 2.5 exposure mediated lung injury - Juan Zhang; Wen-Hao Zhang; Christophe Morisseau; Min Zhang; Hong-Jun Dong; Qi-Meng Zhu; Xiao-Kui Huo; Cheng-Peng Sun; Bruce D. Hammock; Xiao-Chi Ma (Journal of Hazardous Materials, 2023)

Ultrafast self-assembled supramolecular nanoparticles for enhanced chemodynamic therapy and ferroptosis through lactic acid metabolism regulation - Qi Meng; Jia Tan; Weifang Tong; Changxiao Chen; Zhendong Liu; Sainan Liu; Meifang Wang; Ziyong Cheng; Binbin Ding; Ping'an Ma; Jun Lin (Chemical Engineering Journal, 2023)

Impact of land use change on the urban-rural temperature disparity in Eastern China - Yanyu Wang; Jun Wang; Huanxin Zhang; Nathan Janechek; Yi Wang; Meng Zhou; Pengke Shen; Jianguo Tan; Qianshan He; Tiantao Cheng; Cheng Huang (Atmospheric Environment, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Alkylamides from Zanthoxylum armatum DC. and their neuroprotective activity - Qian-Nv Ye; Cheng-Bo Wang; Tian Chai; Jun Wang; Xian-Hua Meng; Xiao-Feng Shi; Jun-Li Yang (Phytochemistry, 2023)

Characterization of modified rice straw biochar in immobilizing Bacillus subtilis 168 and evaluation on its role as a novel agent for zearalenone-removal delivery - Jie Han; Jiao Zhang; Jun Meng; Yuanqi Cai; Mo Cheng; Siyu Wu; Zeming Li (Journal of Hazardous Materials, 2023)

Associations of long-term joint exposure to various ambient air pollutants with all-cause and cause-specific mortality: evidence from a large population-based cohort study - Zhi-Hao Li; Xiao-Meng Wang; Jia-Xuan Xiang; Ying Nan; Ying-Jun Chen; Pei-Dong Zhang; Dan Liu; Dong Shen; Xi-Ru Zhang; Wen-Fang Zhong; Pei-Liang Chen; Qing-Mei Huang; et al. (Environmental Science and Pollution Research, 2023)

Role of macrophage AHR/TLR4/STAT3 signaling axis in the colitis induced by non-canonical AHR ligand aflatoxin B1 - Liwen Zhang; Dong Cheng; Jing Zhang; Hui Tang; Fenghua Li; Yi Peng; Xinglan Duan; En Meng; Cuili Zhang; Tao Zeng; Fuyong Song; Jia-Sheng Wang; et al. (Journal of Hazardous Materials, 2023)

Gastrointestinal digestion fates of lipids based on pH-stat and Caco-2 cells models: Superior bioavailability of triglyceride monomer derived from silkworm pupae oil - Cheng-Hai Yan; Xiao-Meng Xun; Richard A. Herman; Yu-Fan Zhan; Lu-Chan Gong; Fu-An Wu; Jun Wang (Food Bioscience, 2023)

Novel caffeic acid grafted chitosan-sodium alginate microcapsules generated by microfluidic technique for the encapsulation of bioactive peptides from silkworm pupae - Xiao-Meng Xun; Zhi-Ang Zhang; Zi-Xuan Yuan; Kamila Tuhong; Cheng-Hai Yan; Yu-Fan Zhan; Guo-Ping Kang; Qiong-Ying Wu; Jun Wang (Sustainable Chemistry and Pharmacy, 2023)

Severe shoot topping slows down berry sugar accumulation rate, alters the vine growth and photosynthetic capacity, and influences the flavoromics of Cabernet Sauvignon grapes in a semi-arid region - Hao-Cheng Lu; Meng-Bo Tian; Ning Shi; Xiao Han; Hui-Qing Li; Chi-Fang Cheng; Wu Chen; Shu-De Li; Fei He; Chang-Qing Duan; Jun Wang (European Journal of Agronomy, 2023)

Alternating polarization steered CO2 bio-electroreduction selectivity with stepped extracellular electron transfer - Rongxin Xia; Ze Zhang; Zhuo Chen; Xinyi Zhou; Meng Zhang; Junhu Zhou; Jun Cheng (Chemical Engineering Journal, 2023)

Volatomics of ‘Cabernet Sauvignon’ grapes and wines under the fan training system revealed the nexus of microclimate and volatile compounds - Meng-Bo Tian; Yao Liu; Hao-Cheng Lu; Li Hu; Yu Wang; Chi-Fang Cheng; Wu Chen; Shu-De Li; Fei He; Chang-Qing Duan; Jun Wang (Food Chemistry, 2023)

Gold − Titanium dioxide heterojunction for enhanced sonodynamic mediated biofilm eradication and peri-implant infection treatment - Fang Li; Qiyuan Pan; Yun Ling; Jingying Guo; Yaru Huo; Chao Xu; Manwen Xiong; Meng Yuan; Ziyong Cheng; Min Liu; Jun Lin (Chemical Engineering Journal, 2023)

Further undescribed cembranoids from South China Sea soft coral Sarcophyton ehrenbergi: Structural elucidation and biological evaluation - Meng-Jun Wu; Dan-Dan Yu; Ye-Qing Du; Juan Zhang; Ming-Zhi Su; Cheng-Shi Jiang; Yue-Wei Guo (Phytochemistry, 2023)

Observation-based sources evolution of non-methane hydrocarbons (NMHCs) in a megacity of China - Yarong Peng; Hongli Wang; Qian Wang; Shengao Jing; Jingyu An; Yaqin Gao; Cheng Huang; Rusha Yan; Haixia Dai; Tiantao Cheng; Qiang Zhang; Meng Li; et al. (Journal of Environmental Sciences, 2023)

Using fly larvae to convert food waste for growing Oujiang color common carps: health risk assessment of polycyclic aromatic hydrocarbons - Meng Gao; Zhan-Biao Yang; Xiao-Xun Xu; Jun-Ren Xian; Yuan-Xiang Yang; Song Yang; Yu-Bon Man; Zhang Cheng (Environmental Science and Pollution Research, 2023)

Region, vintage, and grape maturity co-shaped the ionomic signatures of the Cabernet Sauvignon wines - Xiao Han; Hao-Cheng Lu; Yu Wang; Xiao-Tong Gao; Hui-Qing Li; Meng-Bo Tian; Ning Shi; Ming-Yu Li; Xiao-Li Yang; Fei He; Chang-Qing Duan; Jun Wang (Food Research International, 2023)

miR-27a-3p targets NR5A2 to regulate CYP19A1 expression and 17-β estradiol synthesis in ovine granulosa cells - Hongbing Gui; Fan Li; Cheng Chen; Qiuyi Zhu; Chenjian Zhang; Jun Zhang; Chunhua Meng; Yong Qian; Shaoxian Cao; Yinxia Li (Animal Reproduction Science, 2023)

Contact toxicity and repellence of essential oil from Senecio scandens and its major components against three stored product insects - Fang He; Jing-Yu Liu; Li-Jiang Chen; Zi-Qian Cheng; Meng-Qi Cheng; Shu-Shan Du; Yu-Li Sang; Yan-Jun Hao (Natural Product Research, 2022)

Petrogenesis and tectonic setting of the early-middle triassic subduction-related granite in the eastern segment of East Kunlun: evidences from petrology, geochemistry, and zircon U-Pb-Hf isotopes - Zuo-Chen Li; Xian-Zhi Pei; Paul D. Bons; Rui-Bao Li; Lei Pei; Guo-Chao Chen; You-Xin Chen; Cheng-Jun Liu; Meng Wang; Shao-Wei Zhao; Xiao-Bing Li; Feng Gao (International Geology Review, 2022)

LATS1 K751 acetylation blocks activation of Hippo signalling and switches LATS1 from a tumor suppressor to an oncoprotein - Siyuan Yang; Weizhi Xu; Cheng Liu; Jiaqi Jin; Xueying Li; Yuhan Jiang; Lei Zhang; Xianbin Meng; Jun Zhan; Hongquan Zhang (Science China Life Sciences, 2022)

Complement C3 Aggravates Post-epileptic Neuronal Injury Via Activation of TRPV1 - Guang-Tong Jiang; Lin Shao; Shuo Kong; Meng-Liu Zeng; Jing-Jing Cheng; Tao-Xiang Chen; Song Han; Jun Yin; Wan-Hong Liu; Xiao-Hua He; Yu-Min Liu; Lanzi Gongga; et al. (Neuroscience Bulletin, 2021)

An efficient genetic manipulation protocol for dark septate endophyte Falciphora oryzae - Zhen-Zhu Su; Meng-Di Dai; Jia-Nan Zhu; Yu-Lan Zeng; Xuan-Jun Lu; Xiao-Hong Liu; Fu-Cheng Lin (Biotechnology Letters, 2021)

Gelidibacter maritimus sp. nov., isolated from marine sediment - Cheng Gao; He-Yuan Lun; Dan-Dan Shang; Min Cai; Meng-Qi Ye; Zong-Jun Du (Archives of Microbiology, 2021)

Association between large artery stenosis, cerebral small vessel disease and risk of ischemic stroke - Fei Han; Ding-Ding Zhang; Fei-Fei Zhai; Jun Xue; Jiang-Tao Zhang; Shuang Yan; Li-Xin Zhou; Jun Ni; Ming Yao; Meng Yang; Ming-Li Li; Zheng-Yu Jin; et al. (Science China Life Sciences, 2021)

Spatiotemporal characteristics and trend assessment of Ms ≥ 5.6 earthquakes in the Tianshan area of China based on co-occurrence analysis and commensurability - Jia Wan; Jun-Ping Yan; Zi-Qiang Liu; Xiao-Meng Wang; Yu-Feng Zhang; Cheng-Bo Wang (Applied Geophysics, 2021)

Proteomics provides individualized options of precision medicine for patients with gastric cancer - Wenwen Huang; Dongdong Zhan; Yazhuo Li; Nairen Zheng; Xin Wei; Bin Bai; Kecheng Zhang; Mingwei Liu; Xuefei Zhao; Xiaotian Ni; Xia Xia; Jinwen Shi; et al. (Science China Life Sciences, 2021)

CD40 induces an antimicrobial response against the intracellular pathogen Streptococcus agalactiae in Nile tilapia, Oreochromis niloticus - Hongli Xia; Huimin Fan; Meng Long; Jun Cheng; Wenjie Chen; Dapeng Yu; Liqun Xia; Yishan Lu (Journal of Fish Diseases, 2021)
Streptococcus agalactiae is a Gram‐positive facultative intracellular bacterium that leads to severe economic loss of tilapia worldwide. Previous studies demonstrated that CD40 contributes to host protection against intracellular injection. In this study, CD40 was characterized from Nile tilapia ( Oreochromis niloticus ), named OnCD40. Sequence analysis showed that open reading frame of OnCD40 was 933 bp, containing a single peptide, a transmembrane domain and four cysteine‐rich domains. The qRT‐PCR revealed that OnCD40 was expressed in all examined tissues with the most abundant ones in spleen and thymus. After S. agalactiae stimulation, the expression of OnCD40 was significantly induced in most of the detected organs. Moreover, OnCD40‐overexpressing fish elicited significant protection against subsequent S. agalactiae challenge; approximately 10000‐fold fewer bacteria were detected in spleen of OnCD40‐overexpressing fish in comparison with control fish. Thus, CD40 had protecting function in Nile tilapia against intracellular pathogens.

Structural characterization and immunosuppressive activity of a new pregnane glycoside from Epigynum cochinchinensis - Yu-Ting Shao; Yan Zhao; Hong Zhang; Meng-Jun Jiang; Afsar Khan; Sheng-Bao Cai; Tian-Rui Zhao; Gui-Guang Cheng; Jian-Xin Cao (Natural Product Research, 2019)

Two new labdane diterpenoids from aerial parts of Leonurus japonicus and their anti-inflammatory activity - Yu-Mei Hu; Wen-Jun Liu; Meng-Xuan Li; Hai-Bo Li; Tao Jiang; Ning-Bo Cheng; Wen-Zhe Huang; Zhen-Zhong Wang; Hua-Xu Zhu; Wei Xiao (Natural Product Research, 2019)

Paleogene organic-walled dinoflagellate cysts in the Shulu Sag, Hebei Province, China - Jin-hui Cheng; Yan-jun Zhao; Fan-wei Meng (Carbonates and Evaporites, 2019)

Retraction Note to: An assessment of transgenomics as a tool for gene discovery in Populus euphratica Oliv. - Jing Zhou; Xin Liu; Shu-Tang Zhao; Jian-Jun Hu; Jie-Wei Zhang; Jie-Hua Wang; Xiao-Peng Peng; Xiao-Li Qi; Tie-Long Cheng; Meng-Zhu Lu (Plant Molecular Biology, 2018)

TMEM88 mediates inflammatory cytokines secretion by regulating JNK/P38 and canonical Wnt/β-catenin signaling pathway in LX-2 cells - Tao Xu; Lin-xin Pan; Yun-xuan Ge; Peng Li; Xiao-ming Meng; Cheng Huang; Jun Li (Inflammopharmacology, 2018)

Novel alternatively spliced isoforms of MEF2A and their mRNA expression patterns in pigs - Xiao Hong Guo; Qi Zhang; Meng Li; Peng Fei Gao; Guo Qing Cao; Zhi Min Cheng; Ning Fang Zhang; Bao Yu Le; Jian Feng Liu; Xiao Jun Liu; Bu Gao Li (Journal of Genetics, 2018)

Identification of Neoscytalidium dimidiatum causing canker disease of pitaya in Hainan, China - Min Xu; Yun Peng; Zhao Qi; Zhen Yan; Lu Yang; Meng-Die He; Qing-Xiu Li; Cheng-Li Liu; Yun-Ze Ruan; Shuang-Shuang Wei; Jun Xie; You-Quan Xia; et al. (Australasian Plant Pathology, 2018)

RETRACTED ARTICLE: An assessment of transgenomics as a tool for gene discovery in Populus euphratica Oliv. - Jing Zhou; Xin Liu; Shu-Tang Zhao; Jian-Jun Hu; Jie-Wei Zhang; Jie-Hua Wang; Xiao-Peng Peng; Xiao-Li Qi; Tie-Long Cheng; Meng-Zhu Lu (Plant Molecular Biology, 2018)

Telmisartan attenuates hydrogen peroxide-induced apoptosis in differentiated PC12 cells - Guan Tao Du; Xuan Ke; Guo Liang Meng; Guang Jun Liu; Hui Ying Wu; Jin Hong Gong; Xiao Dan Qian; Jin Luo Cheng; Hao Hong (Metabolic Brain Disease, 2018)

Nano-silver modifies the vase life of cut herbaceous peony (Paeonia lactiflora Pall.) flowers - Daqiu Zhao; Menglin Cheng; Wenhui Tang; Ding Liu; Siyu Zhou; Jiasong Meng; Jun Tao (Protoplasma, 2018)

An anti-Propionibacterium acnes antibody shows heterologous resistance to an Actinobacillus pleuropneumoniae infection independent of neutrophils in mice - Jian-fang Liu; Qiu-yue Ma; Ri-ning Zhu; Meng-jun Cheng; Chun-tong Bao; Jing-min Gu; Chang-jiang Sun; Paul Richard Langford; Wen-yu Han; Lian-cheng Lei (Immunologic Research, 2017)

Acid sphingomyelinase/ceramide regulates carotid intima-media thickness in simulated weightless rats - Yao-Ping Cheng; Hai-Jun Zhang; Yu-Ting Su; Xing-Xing Meng; Xiao-Ping Xie; Yao-Ming Chang; Jun-Xiang Bao (Pflügers Archiv - European Journal of Physiology, 2017)

Toxicokinetics and internal exposure of acrylamide: new insight into comprehensively profiling mercapturic acid metabolites as short-term biomarkers in rats and Chinese adolescents - Qiao Wang; Xinyu Chen; Yiping Ren; Qing Chen; Zhen Meng; Jun Cheng; Yunyan Zheng; Weijiang Zeng; Qingning Zhao; Yu Zhang (Archives of Toxicology, 2017)

Evaluation of the land carrying capacity of major grain-producing areas and the identification of risk factors - Kun Cheng; Qiang Fu; Song Cui; Tian-xiao Li; Wei Pei; Dong Liu; Jun Meng (Natural Hazards, 2017)

Effects of maize stover and its derived biochar on greenhouse gases emissions and C-budget of brown earth in Northeast China - Xu Yang; Yu Lan; Jun Meng; Wenfu Chen; Yuwei Huang; Xiaoyi Cheng; Tianyi He; Ting Cao; Zunqi Liu; Linlin Jiang; Jiping Gao (Environmental Science and Pollution Research, 2017)

The Regulatory Roles of ncRNA Rli60 in Adaptability of Listeria monocytogenes to Environmental Stress and Biofilm Formation - Ye-long Peng; Qing-ling Meng; Jun Qiao; Kun Xie; Cheng Chen; Tian-li Liu; Zheng-xiang Hu; Yu Ma; Xue-peng Cai; Chuang-fu Chen (Current Microbiology, 2016)

Serological and molecular investigation of porcine sapovirus infection in piglets in Xinjiang, China - Qiao Jun; Tian Lulu; Meng Qingling; Zhang Xingxing; Lu Haiting; Gong Shasha; Cheng Zibing; Cai Xuepeng; Zhang Jinsheng; Zhang Zaichao; Cai Kuojun; Chen Chuangfu (Tropical Animal Health and Production, 2016)

Inhibition of IRF3 expression reduces TGF-β1-induced proliferation of hepatic stellate cells - Ming-ming Ni; Tao Xu; Ya-rui Wang; Ying-hua He; Qun Zhou; Cheng Huang; Xiao-ming Meng; Jun Li (Journal of Physiology and Biochemistry, 2016)

Serological and molecular survey of sheep infected with Mycoplasma ovipneumoniae in Xinjiang, China - Chen Cheng; Qiao Jun; Meng Qingling; Hu Zhengxiang; Ma Yu; Cai Xuepeng; Cheng Zibing; Zhang Jinsheng; Zhang Zaichao; Cai Kuojun; Chen Chuangfu (Tropical Animal Health and Production, 2015)

Expression of serine proteinase P186 of Arthrobotrys oligospora and analysis of its nematode-degrading activity - Hailong Zhao; Jun Qiao; Qingling Meng; Shasha Gong; Cheng Chen; Tianli Liu; Lulu Tian; Xuepeng Cai; Jianxun Luo; Chuangfu Chen (Antonie van Leeuwenhoek, 2015)

Flavobacterium notoginsengisoli sp. nov., isolated from the rhizosphere of Panax notoginseng - Meng-Yue Zhang; Huan Xu; Tian-Yuan Zhang; Jun Xie; Juan Cheng; Salam Nimaichand; Shan-Hui Li; Wen-Jun Li; Yi-Xuan Zhang (Antonie van Leeuwenhoek, 2015)

Complete genome sequence of a new recombinant echovirus 25 strain isolated from a neonatal patient with hand, foot, and mouth disease complicated by encephalitis in Beijing, China - Hongjie Li; Yixing Meng; Lin Pang; Jinqiu Liang; Hongping Lu; Qi Wang; Pu Liang; Jinfeng Cao; Shun-ai Liu; Jun Cheng (Virus Genes, 2015)

Transient receptor potential vanilloid 4 inhibits rat HSC-T6 apoptosis through induction of autophagy - Lei Zhan; Yang Yang; Tao-Tao Ma; Cheng Huang; Xiao-Ming Meng; Lei Zhang; Jun Li (Molecular and Cellular Biochemistry, 2015)

Smad2 protects against TGF-β1/Smad3-mediated collagen synthesis in human hepatic stellate cells during hepatic fibrosis - Lei Zhang; Changwei Liu; Xiao-ming Meng; Cheng Huang; Fengyun Xu; Jun Li (Molecular and Cellular Biochemistry, 2015)

Sinomonas notoginsengisoli sp. nov., isolated from the rhizosphere of Panax notoginseng - Meng-Yue Zhang; Jun Xie; Tian-Yuan Zhang; Huan Xu; Juan Cheng; Shan-Hui Li; Wen-Jun Li; Yi-Xuan Zhang (Antonie van Leeuwenhoek, 2014)

A novel method for determining the anisotropy of geophysical parameters: unit range variation increment (URVI) - Yun-Meng Cao; Zhi-Wei Li; Jian-Chao Wei; Wen-Jun Zhan; Jian-Jun Zhu; Chang-Cheng Wang (Applied Geophysics, 2014)

Efficacy of Various Combined Blood Purification Techniques for Treating Patients with Non-viral Acute Liver Failure - Mao-qin Li; Jia-qiong Li; Zai-xiang Shi; Ji-yuan Xu; Zhou Zhang; Fei Lu; Lin Li; Yan-jun Xu; Xun Mo; Bo Lu; Xiao-meng Wang; Li-li Ma; et al. (Cell Biochemistry and Biophysics, 2014)

Histone deacetylases inhibitor trichostatin A increases the expression of Dleu2/miR-15a/16-1 via HDAC3 in non-small cell lung cancer - Chi-qi Chen; Cheng-shui Chen; Jun-jie Chen; Lian-ping Zhou; Hong-lei Xu; Wei-wei Jin; Jian-bo Wu; Shen-meng Gao (Molecular and Cellular Biochemistry, 2013)

Identification of wheat-Secale africanum chromosome 2Rafr introgression lines with novel disease resistance and agronomic characteristics - Meng-Ping Lei; Guang-Rong Li; Li Zhou; Cheng-Hui Li; Cheng Liu; Zu-Jun Yang (Euphytica, 2013)

Environmental assessment of polycyclic aromatic hydrocarbons in the surface sediments of a remote region on the eastern coast, Taiwan - Jun-Yi Kuo; Fung-Chi Ko; Jing-O Cheng; Pei-Jie Meng; Jan-Jung Li; Chin-Chang Hung (Environmental Monitoring and Assessment, 2012)

Unloading the infarcted heart affect MMPs–TIMPs axis in a rat cardiac heterotopic transplantation model - Wei-jian Wang; Zi-li Meng; Yun-chang Mo; Jun-wei Liu; Cheng-chao Sun; Sheng-shou Hu; Hao Zhang (Molecular Biology Reports, 2012)

Interaction of green tea polyphenol epigallocatechin-3-gallate with sunitinib: potential risk of diminished sunitinib bioavailability - Jun Ge; Ben-Xu Tan; Ye Chen; Li Yang; Xing-Chen Peng; Hong-Ze Li; Hong-Jun Lin; Yu Zhao; Meng Wei; Ke Cheng; Long-Hao Li; Hang Dong; et al. (Journal of Molecular Medicine, 2011)

Viral infection of tobacco plants improves performance of Bemisia tabaci but more so for an invasive than for an indigenous biotype of the whitefly - Jian Liu; Meng Li; Jun-min Li; Chang-jun Huang; Xue-ping Zhou; Fang-cheng Xu; Shu-sheng Liu (Journal of Zhejiang University-SCIENCE B, 2010)

Transgene integration and organization in Cotton (Gossypium hirsutum L.) genome - Jun Zhang; Lin Cai; Jiaqin Cheng; Huizhu Mao; Xiaoping Fan; Zhaohong Meng; Ka Man Chan; Huijun Zhang; Jianfei Qi; Lianghui Ji; Yan Hong (Transgenic Research, 2008)

Salinicoccus salitudinis sp. nov., a new moderately halophilic bacterium isolated from a saline soil sample - Yi-Guang Chen; Xiao-Long Cui; Wen-Jun Li; Li-Hua Xu; Meng-Liang Wen; Qian Peng; Cheng-Lin Jiang (Extremophiles, 2008)

Streptomyces nanningensis sp. nov. a novel Streptomycete from forest soil - Yi Jiang; Wen-Jun Li; Ping Xu; Ming-Gang Li; Meng-Liang Wen; Guan-Hua Du; Li-Hua Xu; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2005)

Streptomyces roseoalbus sp. nov., an actinomycete isolated from soil in Yunnan, China - Li-Hua Xu; Yi Jiang; Wen-Jun Li; Meng-Lang Wen; Ming-Gang Li; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2005)